Pengukuran dan Analisis Capability Level Tata Kelola IT di Laboratorium Teknik Informatika Menggunakan COBIT 5 - Ulya Anisatur Rosyidah; Lintang Setyo Kurniawati (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2026)
This study aims to analyze the capability level of Information Technology (IT) governance at the Informatics Engineering Laboratory of Universitas Muhammadiyah Jember using the COBIT 5 framework, considering the increasing volume of data, growing dependence on IT, and the rising risk of cyber threats that may lead to unauthorized access, data loss, and low operational efficiency if IT governance is not properly implemented. The research methodology includes a literature review, in-depth interviews, questionnaire distribution, and direct observation of laboratory activities. The analysis results indicate that most IT governance processes are at Level 2 (Managed), meaning that the processes are documented and systematically managed but not yet fully standardized or optimized. Several critical areas, particularly information security management, still exhibit weaknesses and require special attention. Through the implementation of COBIT 5, the laboratory can assess the alignment of its IT governance processes with best practices and identify areas that require improvement. Therefore, this study recommends the development of standard operating procedures (SOPs), the implementation of regular training for laboratory staff, and the strengthening of routine monitoring and evaluation mechanisms to enhance the effectiveness and maturity of IT governance on a sustainable basis.